Pengembangan Flashcard Berbasis Pendekatan Saintifik: Media Pembelajaran pada Materi Struktur dan Fungsi Sel - Izza Yani Umaroh; Miza Nina Adlini (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
The purpose of this study was to develop flashcards based on a scientific approach to the material of cell structure and function in order to improve student learning outcomes. The background of this research is the low interest of students in participating in learning due to the lack of interactive learning media which has an impact on low student learning outcomes. The research method used is R&D (Research and Development) research with the ADDIE model which has 5 stages, namely analysis, design, development, implementation and evaluation. The subjects in this study were 22 students of class XI IPA 2 at SMA Swasta Sinar Husni. Flashcards were validated by material experts and media experts and tested for practicality and effectiveness. The results showed that flashcards obtained a percentage of material validity of 84% (very valid) and media validity of 94% (very valid). Flashcards were also declared practical with a percentage of 93% (very practical) from teachers and 84% (very practical) from students. The effectiveness test with an N-Gain score of 0.88 (High) showed that there was a significant increase in student learning outcomes. In conclusion, flashcards based on a scientific approach to cell structure and function material can be declared valid, practical and effective and have the potential to support active learning in biology learning. Keywords: Flashcard, Scientific Approach, Cell Structure and Function